Peran self-esteem sebagai mediator dukungan sosial teman dan keluarga terhadap gangguan psikologis pada mahasiswa - Prasetio, Clement Eko; Triwahyuni, Airin (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2021)
Abstract Students face many demands, both academically and psychologically. The number of demands makes students vulnerable to psychological disorders. Psychological disorders have a negative impact on the lives of students and also the people around them. Students who have social support are thought to have a lower risk of experiencing psychological disorders. This study aims to determine the role of self-esteem as a mediator between social support and psychological disorders. Research participants were 376 students from second to fourth year in a Faculty at X University. Research measurement tools which were used in this study, consist of Perceived Social Support Friends (α =0,860) and Family (α =0,902); Rosenberg Self-Esteem's Scale (α =0,871); and Self-Report Questionnaire (α =0,860). Simple mediation analysis using SPSS, especially PROCESS were used for analyzing the results. The results of the analysis show that self-esteem can mediate the relationship between social support from friends and family with psychological disorders in undergraduate students. The implications of the research results are also discussed. Keywords: College Student; Mediation; Perceived Social Support; Psychological Problems; Self-Esteem Abstrak Mahasiswa menghadapi banyak tuntutan, baik secara akademik maupun psikologis. Banyaknya tuntutan membuat mahasiswa rentan mengalami gangguan psikologis. Gangguan psikologis berdampak negatif bagi kehidupan mahasiswa dan juga orang-orang disekitarnya. Mahasiswa yang memiliki dukungan sosial diduga memiliki risiko lebih rendah untuk mengalami gangguan psikologis. Penelitian ini bertujuan untuk mengetahui peran self-esteem sebagai mediator antara dukungan sosial dengan gangguan psikologis. Sebanyak 376 mahasiswa angkatan 2016-2018 pada sebuah fakultas di Universitas X menjadi partisipan penelitian. Alat ukur penelitian yang digunakan dalam penelitian ini adalah Perceived Social Support Scale Friend (α =0,860) and Family (α =0,902); Rosenberg Self-Esteem’s Scale (α =0,871); dan Self-Report Questionnaire-20 (α =0,860). Teknik analisis yang digunakan adalah analisis mediasi sederhana dengan menggunakan SPSS, khususnya PROCESS. Hasil analisis menunjukkan bahwa self-esteem dapat memediasi hubungan antara dukungan sosial teman dan keluarga dengan gangguan psikologis pada mahasiswa. Implikasi dari hasil penelitian juga ikut serta dibahas. Kata Kunci: Dukungan Sosial; Gangguan Psikologis; Self-Esteem; Mahasiswa; Mediasi